Long-term prednisone treatment causes fungal microbiota dysbiosis and alters the ecological interaction between gut mycobiome and bacteriome in rats - Li, Wenyan; Shu, Yun; Zhang, Jing; Wu, Mengmeng; Zhu, Guang-hua; Huang, Wen-yan; Shen, Li; Kang, Yulin (Frontiers in Microbiology, 2023)
Glucocorticoids (GCs) are widely used in the treatment of immune-mediated diseases due to their anti-inflammatory and immunosuppressive effects. Prednisone is one of the most commonly used GCs. However, it is still unknown whether prednisone affects gut fungi in rats. Herein we investigated whether prednisone changed the composition of gut fungi and the interactions between gut mycobiome and bacteriome/fecal metabolome in rats. Twelve male Sprague-Dawley rats were randomly assigned to a control group and a prednisone group which received prednisone daily by gavage for 6 weeks. ITS2 rRNA gene sequencing of fecal samples was performed to identify differentially abundant gut fungi. The associations between gut mycobiome and bacterial genera/fecal metabolites obtained from our previously published study were explored by using Spearman correlation analysis. Our data showed that there were no changes in the richness of gut mycobiome in rats after prednisone treatment, but the diversity increased significantly. The relative abundance of genera Triangularia and Ciliophora decreased significantly. At the species level, the relative abundance of Aspergillus glabripes increased significantly, while Triangularia mangenotii and Ciliophora sp. decreased. In addition, prednisone altered the gut fungi-bacteria interkingdom interactions in rats after prednisone treatment. Additionally, the genus Triangularia was negatively correlated with m-aminobenzoic acid, but positively correlated with hydrocinnamic acid and valeric acid. Ciliophora was negatively correlated with phenylalanine and homovanillic acid, but positively correlated with 2-Phenylpropionate, hydrocinnamic acid, propionic acid, valeric acid, isobutyric acid and isovaleric acid. In conclusion, long-term prednisone treatment caused fungal microbiota dysbiosis and might alter the ecological interaction between gut mycobiome and bacteriome in rats.